Physiotherapy Management for Osteoarthritis Knee: A Case Study - Wardhani, Azzahra Irkoshaum Kusuma; Naufal, Adnan Faris (Academic Physiotherapy Conference Proceeding, 2022)
Introduction: Osteoarthritis (OA) is the most common form of arthritis affecting approximately 302 million people worldwide. OA is characterized by pathology involving the entire joint including cartilage degradation, bone remodeling, synovial inflammatory osteophyte formation, leading to pain, stiffness, swelling, and loss of normal joint function. The most commonly affected appendicular joints include: knees, hips and hands. Conservative therapy consists of pharmacological and non-pharmacological therapy given to patients with mild tomoderatekneeOA.Nonpharmacologicaltherapy can be in the form of exercise therapy and physical modalities. The purpose of this study was to determine the effectiveness of a physiotherapy program using Ultrasound, TENS, Quadriceps Setting and Passive Hamstring Exercise.Case Presentation: Patients with the initials Mr. M is 60 years old with the main job as a sand porter. Nine months ago, the patient fell under a sandbag while working and hit his head and back. As a result, the back fractured and had to be operated on. One week after surgery the patient had a urinary tract disorder, so he needed to be operated on again. As a result of the operation the patient was required to use a catheter. The patient began to complain of stiffness due to the use of the catheter and bed rest in the long term (8 months). Management and Outcome: The patient attended therapy three times in two weeks with a physiotherapy programs Ultrasound, TENS, Quadriceps Setting and Passive Hamstring Exercise. Patient were evaluated using Numerical Rating Scale (NRS), Meter line, Goniometer, and Manual Muscle Testing (MMT),Conclusion: Physiotherapy with the intensity of patient visits three times in two weeks with the intervention of Ultrasound, TENS, Quadriceps Setting and Passive Hamstring Exercise can reduce pain, decrease edema, improve leg muscle strength, and increase range of motion of knee joint.